KONSEP PENDIDIKAN ISLAM MODERAT PRESPEKTIF M. QURAISH SHIHAB DALAM MENGATASI PERBUDAKAN MASA KINI (study kitab wasathiyyah) - Mas'ud, Ibnu; Ahmad Yenuri, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Modern slavery has transformed into human trafficking through debt bondage, digital contracts, and social media recruitment. As many as 33.22% of Indonesian Migrant Workers are high school/vocational school graduates who are vulnerable to exploitation due to limited safe migration literacy and weak moral courage. This study aims to: 1) Analyze the concept of moderate Islamic education from M. Quraish Shihab’s perspective in the book Wasathiyyah; 2) Formulate solutions from that moderate Islamic education for addressing modern slavery.This study employed a library research method with a content analysis approach. The primary source is the book Wasathiyyah: Wawasan Islam tentang Moderasi Beragama by M. Quraish Shihab 2019. Data were analyzed through reduction, presentation, and conclusion drawing using the maqashid syariah framework.The results show that the concept of moderate Islamic education is built on three aspects: 1) The aqidah of tawhid liberates individuals from the slave mentality of thama’; 2) Sharia-based fiqh serves as a legal safeguard prohibiting gharar contracts and document withholding; 3) The ethics of i’tidal fosters ghairah as moral courage to report without anarchy. Its actualization is realized through a fiqh curriculum based on case studies of Trafficking in Persons (TIP), a project-based learning method “Recognize Job Scams”, and institutional collaboration with BP2MI and the Ministry of Women’s Empowerment and Child Protection (KemenPPPA). Challenges to actualization include the lack of competent teachers and the faster adaptation of traffickers’ tactics compared to educational institutions. The novelty of this study lies in the theological-juridical-ethical bridge that positions wasathiyyah as a preventive action curriculum, not merely a discourse.